Physical Properties of Superbulky Lanthanide Metallocenes: Synthesis and Extraordinary Luminescence of [EuII(CpBIG)2] (CpBIG=(4‐nBu‐C6H4)5‐Cyclopentadienyl). Issue 37 (31st July 2013) - Harder, Sjoerd; Naglav, Dominik; Ruspic, Christian; Wickleder, Claudia; Adlung, Matthias; Hermes, Wilfried; Eul, Matthias; Pöttgen, Rainer; Rego, Daniel B.; Poineau, Frederic; Czerwinski, Kenneth R.; Herber, Rolfe H.; et al.
Abstract The superbulky deca‐aryleuropocene [Eu(CpBIG)2], CpBIG=(4‐nBu‐C6H4)5‐cyclopentadienyl, was prepared by reaction of [Eu(dmat)2(thf)2], DMAT=2‐Me2N‐α‐Me3Si‐benzyl, with two equivalents of CpBIGH. Recrystallizyation from cold hexane gave the product with a surprisingly bright and efficient orange emission (45 % quantum yield). The crystal structure is isomorphic to those of [M(CpBIG)2] (M=Sm, Yb, Ca, Ba) and shows the typical distortions that arise from CpBIG⋅⋅⋅CpBIG attraction as well as excessively large displacement parameter for the heavy Eu atom (Ueq=0.075). In order to gain information on the true oxidation state of the central metal in superbulky metallocenes [M(CpBIG)2] (M=Sm, Eu, Yb), several physical analyses have been applied. Temperature‐dependent magnetic susceptibility data of [Yb(CpBIG)2] show diamagnetism, indicating stable divalent ytterbium. Temperature‐dependent 151Eu Mössbauer effect spectroscopic examination of [Eu(CpBIG)2] was examined over the temperature range 93–215 K and the hyperfine and dynamical properties of the EuII species are discussed in detail. The mean square amplitude of vibration of the Eu atom as a function of temperature was determined and compared to the value extracted from the single‐crystal X‐ray data at 203 K. The large difference in these two values was ascribed to the presence of static disorder and/or the presence of low‐frequency torsional and librational modes in [Eu(CpBIG)2]. X‐ray absorbance near edge spectroscopy (XANES) showed that all three [Ln(CpBIG)2] (Ln=Sm, Eu, Yb) compounds are divalent. The XANES white‐line spectra are at 8.3, 7.3, and 7.8 eV, for Sm, Eu, and Yb, respectively, lower than the Ln2O3 standards. No XANES temperature dependence was found from room temperature to 100 K. XANES also showed that the [Ln(CpBIG)2] complexes had less trivalent impurity than a [EuI2(thf)x] standard. The complex [Eu(CpBIG)2] shows already at room temperature strong orange photoluminescence (quantum yield: 45 %): excitation at 412 nm (24270 cm−1) gives a symmetrical single band in the emission spectrum at 606 nm (νmax=16495 cm−1, FWHM: 2090 cm−1, Stokes‐shift: 2140 cm−1), which is assigned to a 4f65d1→4f7 transition of EuII. These remarkable values compare well to those for EuII‐doped ionic host lattices and are likely caused by the rigidity of the [Eu(CpBIG)2] complex. Sharp emission signals, typical for EuIII, are not visible.